The Effect of Hand Rehabilitation Treatment on Patients Operated for Ganglion Cyst of The Wrist in Own Material - Anna Deskur; Zbigniew Deskur (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The aim of the study was to evaluate the effect of rehabilitation treatment to improve the treatment results of patients operated for ganglions of the wrist. We studied the hands of 77 patients with ganglions of the wrist. 43 women and 34 men aged between 16 and 98 years participated in the study. The open method was used in the surgical treatment to remove the wrist ganglions in all the patients. In the post-operative treatment 46 patients (group I) underwent hand rehabilitation treatment under the supervision of the authors and 31 patients (group II) did not undergo such a treatment. The examination was carried out on all the patients before surgery and at weeks 1 and 4 after surgery. The patients with ganglions of the wrist and pain, impaired hand mobility and impaired hand efficiency were qualified for the surgical treatment. In the rehabilitation treatment stretching exercises were performed as well as loosening and stabilizing the hand and teaching the patients the correct positioning of the upper limb during work and physical activity. The results were statistically analyzed using non-parametric tests such as the chi-square test, signs test and Mann-Whitney test. It was found that in patients after surgical removal of the wrist ganglion rehabilitation treatment has led to the resolution of pain syndromes, movement disorders and efficiency of hand.